Veraneio, turismo de sol e praia e imobiliário-turístico: a formação da região turística entre o litoral Sul de Sergipe e o litoral Norte da Bahia - Santos, Priscila Pereira (2019)
The territorial fluidity between the Southern Coast of Sergipe and the North Coast of Bahia connects Aracaju (SE) and Salvador (BA) and points to the formation of a new reticular urban-regional logic, dynamized by the following regionalizing elements: summer, tourism sun and beach and the real estate-tourist. In this territorial interconnection, this regionalizing triad stands out in the municipalities of Estância, Sul de Sergipe, specifically in Praia do Saco, and Mata de São João, North Coast of Bahia, with relief in Praia do Forte. In this context, it is defended the thesis that from the coastal road articulation between Aracaju (SE) and Salvador (BA), the territorial dynamics of summer, sun and beach tourism and real-estate tourism between the municipalities of Estância, Litoral Sul of Sergipe and Mata de São João, in the North Coast of Bahia, tend to set up, between these coastlines, and territory-network, between Saco Beach (SE) and Praia do Forte (BA), a region tourism under the aegis of the State and the Tourism and Real Estate Market. In this way, the general objective of this research was to analyze the territorial dynamics of summer, sun and beach tourism and tourism-real estate between the Southern Coast of Sergipe and the Northern Coast of Bahia under the perspective of the formation of a tourist region. This proposal of analysis is anchored in the post-structuralist method. Post-structuralism defends the movement of the diversity of thought, the multiple possibilities of analyzing the realities that are put to the researcher. The methodological procedures used were: bibliographic, documentary and field research. The experience and the re-interpretation of the realities of the analyzed subjects were based on simple, systematic and participant observation. Field annotations, photographic records, semi-structured interviews, guidelines and focus were the methodological tools used in field research. The agents and subjects interviewed were interpreted through Discourse Analysis (AD). The historical-genetic structure of the expansion and territorial extensification of the second residence between the North Coast of Bahia and the South Coast of Sergipe connects these coasts while articulating the particularities of Praia do Forte and Saco Beach. Both are characterized by the territorial density of the second residence. Thus, the urban-regional contexts are broadened by the structural peculiarities of the second residence, or, in other words, by the historical continuities. But when connecting in network territories due to their peculiarities, Praia do Forte and Praia do Saco disconnect in the face of the singularities, or rather the discontinuities of the different temporalities and territorialities in the global-regional-local scalar articulation, it is the territorial diversity (re) (de) building the structures of the power game of globalization. In this context, the formation of the tourist region between the Southern Coast of Sergipe and the Northern Coast of Bahia as product-producer of processes of spatial differentiation, as product-producer of globalizing dynamics and of socio-spatial fragmentation in the articulation between the State and the Market, concomitantly the tourist region is also built through the action of different social subjects.